Adapting Peer Researcher Facilitated Strategies to Recruit People Receiving Mental Health Services to a Tobacco Treatment Trial - Baker, Amanda L.; McCarter, Kristen; Brophy, Lisa; Castle, David; Kelly, Peter J.; Cocks, Nadine; McKinlay, Melissa L.; Brasier, Catherine; Borland, Ron; Bonevski, Billie; Segan, Catherine; Baird, Donita E.; et al. (Frontiers in Psychiatry, 2022)
Introduction One of the most challenging aspects of conducting intervention trials among people who experience severe mental illness and who smoke tobacco, is recruitment. In our parent ‘QuitLink’ randomised controlled trial (RCT), slower than expected peer facilitated recruitment, along with the impact of COVID-19 pandemic restrictions, necessitated an adaptive recruitment response. The objectives of the present study were to: (i) describe adaptive peer researcher facilitated recruitment strategies; (ii) explore the effectiveness of these strategies; (iii) investigate whether recruitment strategies reached different subgroups of participants; and (iv) examine the costs and resources required for implementing these strategies. Finally, we offer experience-based lessons in a Peer Researcher Commentary. Methods People were included in the RCT if they smoked at least 10 cigarettes a day and were accessing support for a mental health or alcohol and other drug use issue in Victoria, Australia. Recruitment occurred over two years. We began with peer facilitated recruitment strategies delivered face-to-face, then replaced this with direct mail postcards followed by telephone contact, or online recruitment. Differences between recruitment strategies on key participant variables were assessed. We calculated the average cost per enrollee of the different recruitment approaches. Results Only 109 people were recruited from a target of 382: 29 via face-to-face (March 2019 to April 2020), 66 from postcards (May 2020 to November 2020), and 14 from online (November to December 2020 and January to March 2021) strategies. Reflecting our initial focus on recruiting from supported independent living accommodation facilities, participants recruited face-to-face were significantly more likely to be living in partially or fully supported independent living (n = 29, <0.001), but the samples were otherwise similar. After the initial investment in training and equipping peer researchers, the average cost of recruitment was AU$1,182 per participant – approximately US$850. Face to face recruitment was the most expensive approach and postcard recruitment the least (AU$1,648 and AU$928 per participant). Discussion Peer researcher facilitated recruitment into a tobacco treatment trial was difficult and expensive. Widely dispersed services and COVID-19 restrictions necessitated non-face-to-face recruitment strategies, such as direct mail postcards, which improved recruitment and may be worthy of further research.